2014
DOI: 10.3390/v6072623
|View full text |Cite
|
Sign up to set email alerts
|

Phages Preying on Bacillus anthracis, Bacillus cereus, and Bacillus thuringiensis: Past, Present and Future

Abstract: Many bacteriophages (phages) have been widely studied due to their major role in virulence evolution of bacterial pathogens. However, less attention has been paid to phages preying on bacteria from the Bacillus cereus group and their contribution to the bacterial genetic pool has been disregarded. Therefore, this review brings together the main information for the B. cereus group phages, from their discovery to their modern biotechnological applications. A special focus is given to phages infecting Bacillus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
67
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 187 publications
1
67
0
1
Order By: Relevance
“…Φ29, along with other protein-primed genome replication phages, such as PRD1 or Cp-1 (28, 29), can undergo a lytic cycle only after infection of the host cell occurs. In contrast, phage Bam35, which infects Bacillus thuringiensis and related tectiviruses infecting Bacillus cereus sensu lato group (30,31), are temperate viruses that can self-replicate as linear episomes within lysogenic cells.In this work, we describe the biochemical properties of Bam35 DNA polymerase (B35DNAP) as a faithful, processive DNAP endowed with intrinsic strand displacement activity. Surprisingly, we also found that, despite its high fidelity, it can elude to some Significance Functional classification of DNA polymerases (DNAPs) usually divides them into replicative faithful replicases and error-prone enzymes devoted to DNA repair and DNA damage tolerance through translesion synthesis (TLS).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Φ29, along with other protein-primed genome replication phages, such as PRD1 or Cp-1 (28, 29), can undergo a lytic cycle only after infection of the host cell occurs. In contrast, phage Bam35, which infects Bacillus thuringiensis and related tectiviruses infecting Bacillus cereus sensu lato group (30,31), are temperate viruses that can self-replicate as linear episomes within lysogenic cells.In this work, we describe the biochemical properties of Bam35 DNA polymerase (B35DNAP) as a faithful, processive DNAP endowed with intrinsic strand displacement activity. Surprisingly, we also found that, despite its high fidelity, it can elude to some Significance Functional classification of DNA polymerases (DNAPs) usually divides them into replicative faithful replicases and error-prone enzymes devoted to DNA repair and DNA damage tolerance through translesion synthesis (TLS).…”
mentioning
confidence: 99%
“…Φ29, along with other protein-primed genome replication phages, such as PRD1 or Cp-1 (28,29), can undergo a lytic cycle only after infection of the host cell occurs. In contrast, phage Bam35, which infects Bacillus thuringiensis and related tectiviruses infecting Bacillus cereus sensu lato group (30,31), are temperate viruses that can self-replicate as linear episomes within lysogenic cells.…”
mentioning
confidence: 99%
“…The latter comprises bacteriophages that infect B. thuringiensis, such as Bam35, Gil01, and Gil16 (3); B. anthracis, such as AP50 and Wip1 (4,5); and B. cereus, such as Sole or Simila (6,7). Contrary to most temperate bacteriophages, members of this group are not integrative viruses; rather, they replicate as linear episomic plasmids during the lysogenic cycle (8), in which late phage functions are suppressed (9).…”
mentioning
confidence: 99%
“…Tectiviruses infecting the B. cereus group are, so far, the only known prophages that can reside as autonomously replicating linear plasmids undergoing a lysogenic state in members of this bacterial group (16). Recently, it was shown that two of the most important bioinsecticide serovars of B. thuringiensis used worldwide (i.e., B. thuringiensis serovar kurstaki and B. thuringiensis serovar israelensis) are infected by tectiviruses (18).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the linear molecule is a temperate phage, named GIL01, which is able to reside and replicate independently as a linear plasmid inside the host cell and to produce viable phage particles after induction by DNA-damaging treatments (14). Phage GIL01 and its closest fully sequenced siblings, Bam35, GIL16, AP50, and Wip1, belong to the family Tectiviridae, whose members are icosahedral phages characterized by the presence of an internal lipid membrane/vesicle that, upon adsorption, can act as a tail-like structure for genome delivery (15,16). Beside these 5 fully sequenced representatives, 52 other novel putative tectiviruses infecting the B. cereus group have recently been discovered, among which are various GIL01-and GIL16-like phages infecting B. thuringiensis strains (17,18).…”
mentioning
confidence: 99%